2018
DOI: 10.1126/scisignal.aam8705
|View full text |Cite
|
Sign up to set email alerts
|

The depalmitoylase APT1 directs the asymmetric partitioning of Notch and Wnt signaling during cell division

Abstract: Asymmetric cell division results in two distinctly fated daughter cells. A molecular hallmark of asymmetric division is the unequal partitioning of cell fate determinants. We have previously established that growth factor signaling promotes protein depalmitoylation to foster polarized protein localization, which in turns drives migration and metastasis. Here, we report protein palmitoylation as a key mechanism for the asymmetric partitioning of the cell fate determinants Numb and β-catenin through the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 89 publications
0
19
1
Order By: Relevance
“…(legend on next page) observed in tissues (Goulas et al, 2012;Lechler and Fuchs, 2005) but was different from the asymmetric division in suspension observed for Numb, which is non-polar in interphase cells and becomes asymmetrically partitioned during cell division (Stypulkowski et al, 2018;Tosoni et al, 2015; Figures S4G and S4H). To further quantify Integrin-a6 inheritance, we analyzed Stat3-inhibitor-treated NMMECs and TDMMECs by using fluorescence-activated cell sorting.…”
Section: Stat3-regulated Mitotic Spindle Orientation Controls Integricontrasting
confidence: 57%
“…(legend on next page) observed in tissues (Goulas et al, 2012;Lechler and Fuchs, 2005) but was different from the asymmetric division in suspension observed for Numb, which is non-polar in interphase cells and becomes asymmetrically partitioned during cell division (Stypulkowski et al, 2018;Tosoni et al, 2015; Figures S4G and S4H). To further quantify Integrin-a6 inheritance, we analyzed Stat3-inhibitor-treated NMMECs and TDMMECs by using fluorescence-activated cell sorting.…”
Section: Stat3-regulated Mitotic Spindle Orientation Controls Integricontrasting
confidence: 57%
“…APT enzymes have been studied nearly exclusively in cancer cell models, where APT1 and APT2 inhibition represses oncogenic signaling and stem cell-like features by modulating lateral polarity complexes 5 and asymmetric cell division 29 . Surprisingly, APT1 −/− /APT2 −/− mice are viable and have no overt developmental defects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the zebrafish canonical Wnt ligands have reported that Wnt palmitoylation is essential for activation of signaling but may be dispensable for secretion ( Luz et al, 2014 ; Azbazdar et al, 2019 ). APT1-mediated depalmitoylation has been shown to be important for asymmetric localization of β-catenin and Wnt signaling activity during development ( Stypulkowski et al, 2018 ). Interestingly, Drosophila WntD does not appear to undergo any glycolysis and acylation ( Ching et al, 2008 ).…”
Section: Initiation Of Wnt Signaling At the Plasma Membranementioning
confidence: 99%